Pemberdayaan Masyarakat Dalam Rangka Peningkatan Ketahanan Pangan Di RT 14 Puri Masurai 1, MENDALO INDAH, KABUPATEN MUARO JAMBI - Revis Asra; Dawam Suprayogi; Edwin Permana; Intan Lestari; Muhammad Razi A (CV. ITTC INDONESIA, 2025)
The RT 12 and RT 14 areas of Puri Masurai 1 are mostly occupied by boarding students and residents with neglected yards and low environmental awareness. However, these areas hold great potential for local food security through urban farming. This program aims to increase community awareness and participation in utilizing home yards, support family food security through fast-growing crops, create a clean and green environment, and promote a planting culture among residents and students. Main issues include unproductive yards, poor waste management, and lack of training. The solutions include providing horticultural seeds, verticulture training, and collective community activities. Implemented from June to October 2025, the program involved surveys, preparation of learning media, socialization, and field practice. The results show improved cooperation among residents, successful cultivation of vegetables and fruits, enhanced farming skills, and a cleaner, greener, and more productive environment that helps reduce household expenses.